Effects of blended learning pedagogical practices on students' motivation and autonomy for the teaching of short stories in upper secondary English - Wong, Kung-Teck; Hwang, Gwo-Jen; Choo Goh, Pauline Swee; Mohd Arrif, Siti Khadijah (Interactive learning environments, 2020)
This research was conducted to determine the effectiveness of blended learning on academic achievements, motivation and learner autonomy. The scope of this research is the teaching of English through short stories. A quasi-experimental study was conducted among 116 upper secondary students and two different teaching pedagogies were utilised; a blended learning classroom for the experimental groups, and meanwhile conventional learning classroom for the control groups. The data for students' academic achievement were collected from a post-test questionnaire, whereas data for motivation and learner autonomy were collected through sets of questionnaires adapted from the previous literature. The differences between the two groups were then analysed using the independent t-test. The findings revealed that there was no significant difference in their academic achievements however, there were positive effects on both learner autonomy and students' motivation constructs in the blended learning compared to the conventional learning. The implication of this study is that blended learning is suitable to be implemented in secondary school English classes as long as there are sufficient monetary, equipment and technical supports.